Market Leader Upper Intermediate Business English Teachers Book. New Edition - Mascull, Bill., Heitler, David (Harlow Pearson Education Limited, 2009)
Market Leader Intermediate New Edition retains the dynamic and effective approach to business English that has made the course so successful in classes worldwide. With its new listening content and thoroughly updated material from authenticbusiness such as the Financial Times, it reflects the fast-changing world of business.
Keywords: English Practice